Resolusi konflik dalam pelatihan menulis cerpen bagi mahasiswa Fakultas Teknologi Industri Universitas Atma Jaya Yogyakarta - L. Bening Parwita Sukci; Parama Kartika Dewa; Kristanto Agung Nugroho (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Students learning technology tend to focus more on academic achievement than soft skills. They do not notice what happens around them. On the other hand, they are expected to solve problems in society. Finding a solution requires the ability to think critically, sympathize, and emphatize. This research tries to help students develop their critical thinking, sympathy and empathy from literature as a medium to build the Indonesian character. The characters and events in literature can be role models to behave I society. Students use conflict resolution method to identify problems by scrutinizing the characters, problems and reasons of the actions, as well as applying critical thinking, sympathy and empathy on the characters and then develop and outline and a short story with a different perspective. The training involved nine students from the Departments of Industrial engineering, Informatics and Information Systems resulting in seven stories with various genres and endings. The stories show that students can use their critical and creative thinking using different perspectives, sympathy and empathy in developing a solution and present it in the form of interesting literature works that do not preach.